2010
DOI: 10.1111/j.1364-3703.2009.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene perception via ETR1 is required in Arabidopsis infection by Verticillium dahliae

Abstract: Vascular wilts caused by Verticillium spp. are very difficult to control and, as a result, are the cause of severe yield losses in a wide range of economically important crops. The responses of Arabidopsis thaliana mutant plants impaired in known pathogen response pathways were used to explore the components in defence against Verticillium dahliae. Analysis of the mutant responses revealed enhanced resistance in etr1-1[ethylene (ET) receptor mutant] plants, but not in salicylic acid-, jasmonic acid- or other E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 80 publications
(191 reference statements)
3
67
0
3
Order By: Relevance
“…The triggering of the PDF1.2 expression by K165 is consistent with the data showing that PGPR-primed plants often display JA-dependent defense responses upon pathogen invasion (Pieterse et al 1998;Pozo et al 2008;van Hulten et al 2006). However, since JA-related mutants did not show changes in disease severity caused by V. dahliae or V. longisporum, JA-signaling might be of less importance in the presently studied system (Johansson et al 2006;Pantelides et al 2010;Veronese et al 2003). JA/ET-mediated defense responses are considered as more effective against necrotrophic than biotrophic pathogens (Glazebrook 2005) and, although most reports indicate a mutually antagonistic interaction between SA-and JA-dependent signaling, synergistic interactions have been described as well (Mur et al 2006).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The triggering of the PDF1.2 expression by K165 is consistent with the data showing that PGPR-primed plants often display JA-dependent defense responses upon pathogen invasion (Pieterse et al 1998;Pozo et al 2008;van Hulten et al 2006). However, since JA-related mutants did not show changes in disease severity caused by V. dahliae or V. longisporum, JA-signaling might be of less importance in the presently studied system (Johansson et al 2006;Pantelides et al 2010;Veronese et al 2003). JA/ET-mediated defense responses are considered as more effective against necrotrophic than biotrophic pathogens (Glazebrook 2005) and, although most reports indicate a mutually antagonistic interaction between SA-and JA-dependent signaling, synergistic interactions have been described as well (Mur et al 2006).…”
Section: Discussionsupporting
confidence: 86%
“…It is also known that ET modulates EFR-triggered immunity (Tintor et al 2013). In parallel, the ET receptor ETR1 is a susceptibility factor for V. dahliae and V. longisporum (Johansson et al 2006;Pantelides et al 2010). Thus, it is tempting to speculate from those observations that Verticillium takes advantage of components of EFRregulated immunity to infect the plant.…”
Section: Discussionmentioning
confidence: 99%
“…The role of SA in V. dahliae resistance has always been controversial. Although some SA mutants showed no significant changes in resistance to V. dahliae, more evidence has shown that SA does play a critical role in the resistance (Tjamos et al 2005;Pantelides et al 2010). SA and MeJA were therefore found to be the two major factors influencing Gbvdr5 signaling as Ve1.…”
Section: Generation and Analysis Of Transgenic Cottonmentioning
confidence: 94%
“…Many reports have stated that the roles of ethylene in defense against V. dahliae were through complex mechanisms. Results indicated that the ET mutants, etr1-1 and ein3-1, showed enhanced resistance (Pantelides et al 2010). In cotton, some factors involved in ethylene signal transduction such as GbERF1, GbERF2, ACO1, ACO3, EIN2, and ERF1 were found to be induced by V. dahliae (Zuo et al 2005(Zuo et al , 2007Wang et al 2011;Xu et al 2011).…”
Section: Introductionmentioning
confidence: 96%
“…Interestingly, Pantelides et al (2010) suggest that Verticillium dahliae requires ETR1 to enhance pathogenicity during Arabidopsis infection. Once again, those two pathogens showed a very similar feature of infection phase in Arabidopsis.…”
mentioning
confidence: 99%